METHODOLOGICAL FEATURES OF THE USE OF PROBLEM METHODS IN TEACHING NATURAL SCIENCES IN PRIMARY SCHOOLS - М.И.Нуриддинова (FAN VA TA’LIM INTEGRATSIYASI (INTEGRATION OF SCIENCE AND EDUCATION), 2024)
This article analyzes the methodological features of the use of innovative methods in the teaching of natural sciences in primary school. It discusses the advantages of organizing science lessons on the basis of modern technologies, provides information on the widespread use of didactic games, integration methods, problem-based learning methods in the teaching process. In particular, the use of problem-based methods in the teaching of natural sciences has been analyzed in detail and appropriate conclusions have been drawn on this basis.